2023
DOI: 10.3390/ijms24119318
|View full text |Cite
|
Sign up to set email alerts
|

VvPL15 Is the Core Member of the Pectate Lyase Gene Family Involved in Grape Berries Ripening and Softening

Abstract: The process of ripening and softening in grape begins at veraison and is closely related to the depolymerization of pectin components. A variety of enzymes are involved in pectin metabolism and one class of enzyme, pectin lyases (PLs), have been reported to play an important role in softening in many fruits; however, little information is available on the VvPL gene family in grape. In this study, 16 VvPL genes were identified in the grape genome using bioinformatics methods. Among them, VvPL5, VvPL9, and VvPL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…This is in line with prior studies highlighting the influence of grape variety on amino acid composition and its implications for wine flavor, as noted by Murillo-Peña et al [23] and Moukarzel et al [24]. Moreover, the observed changes in amino acid content emphasize the necessity of precise harvesting decisions to ensure the desired flavor profiles in wines, as discussed in previous research by Ma et al [25]. The study also corroborates the intricate interplay between genetics, metabolism, and environmental conditions in shaping amino acid profiles in grapes.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with prior studies highlighting the influence of grape variety on amino acid composition and its implications for wine flavor, as noted by Murillo-Peña et al [23] and Moukarzel et al [24]. Moreover, the observed changes in amino acid content emphasize the necessity of precise harvesting decisions to ensure the desired flavor profiles in wines, as discussed in previous research by Ma et al [25]. The study also corroborates the intricate interplay between genetics, metabolism, and environmental conditions in shaping amino acid profiles in grapes.…”
Section: Discussionsupporting
confidence: 91%
“…Developing methods without influencing the edible and appealing aspects of fruit, including color, aroma, or nutritional value, has currently become the major goal for controlling softening [4]. It has been suggested that the antisense expression of the FaPLc gene in strawberry did not affect the fruit color [22]; while overexpression of VvPL15 in tomato accelerated the fruit ripening and coloring [14]. In the present study, we found that overexpression of FaPL1 significantly increased anthocyanin content (Figure 7A).…”
Section: Discussionsupporting
confidence: 50%
“…Due to their important roles in a broad range of physiological processes associated with pectin degradation, such as plant growth, development, fruit softening and ripening, PL genes have been identified in various plant species. It has been reported that a total of 26, 20, 12, 46, 22, and 16 PL family members were identified in Arabidopsis [24], peach [13], rice [25], Brassica rapa [26], tomato [19], and grape [14], respectively. In strawberry, several FaPL genes were obtained from multiple varieties, including FaPLa, FaPLb, and FaPLc, from 'Chandler', FaSCPL from 'Sweet Charlie', FaTPL from 'Toyonoka', and five subtype sequences from 'Elsanta' [20,21,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations